2020
DOI: 10.1111/ipd.12683
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward brushing children's teeth—A study among parents with immigrant status in Norway

Abstract: Background: Early childhood caries (ECC) is a common chronic childhood disease with multifactorial etiology including poor parental dietary and hygiene behaviors. Aim: This study aimed to assess toothbrushing-related perceptions among parents with immigrant background living in Norway. Design: A structured interview was performed with immigrant parents to assess their oral health-related knowledge, beliefs, and attitude toward toothbrushing. Immigrant parents of non-Western origin with newborn infants (0-6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Mustafa et al [48] investigated toothbrushing-related perceptions of parents living in Norway with MI background and found that 40% of parents have knowledge about caries as a common disease among children and that 80% of them are aware of the importance of toothbrushing in primary teeth. Moreover, it was demonstrated that oral attitudes were more favorable among MI who had lived in Norway for more than 6 years.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Mustafa et al [48] investigated toothbrushing-related perceptions of parents living in Norway with MI background and found that 40% of parents have knowledge about caries as a common disease among children and that 80% of them are aware of the importance of toothbrushing in primary teeth. Moreover, it was demonstrated that oral attitudes were more favorable among MI who had lived in Norway for more than 6 years.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…Our review included thirteen articles analyzing the oral heath in children/adolescents with age ranging from 0 to 19 years old [39,42,45,46,[48][49][50][51][53][54][55]57,58]. Almost all the studies [39,42,45,46,49,51,54,55] recorded a better oral condition in native children of the control groups compared to the MI groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations